Successful treatment of hepatic oligometastases with stereotactic ablative radiotherapy and radiofrequency ablation in an anaplastic lymphoma kinase fusion‐positive lung cancer patient. Issue 1 (3rd October 2015) - Weber, Britta; Liu, Mitchell; Sobkin, Paul; Morris, Stephan W.; Hout, David; van der Westhuizen, Nicholas; Tonseth, R. Petter; Saltman, David L.
Abstract : Local ablative therapy with stereotactic ablative radiotherapy may improve survival in oncogene‐addicted lung cancer patients with extracranial oligometastatic disease treated with targeted therapies. There is limited data on the use of radiofrequency ablation (RFA) in this same setting. We present a case of an anaplastic lymphoma kinase (ALK)‐positive lung cancer patient with hepatic oligometastatic progression who was successfully treated with both stereotactic ablative radiation and RFA while continuing with an ALK inhibitor. Abstract : Progression of lung cancer may be limited (oligometastatic) or more widespread. We investigated the use of stereotactic ablative radiotherapy (SABR) and radiofrequency ablation (RFA) to treat hepatic oligometastatic disease in a woman with anaplastic lymphoma kinase (ALK) fusion‐positive lung cancer receiving ALK inhibitors.